Trends and Reported Complications in Ankle Arthroplasty and Ankle Arthrodesis in the State of New York, 2009-2018. Issue 3 (August 2022) - Brodeur, Peter G.; Walsh, Devin F.; Modest, Jacob M.; Salameh, Motasem; Licht, Aron H.; Hartnett, Davis A.; Gil, Joseph; Cruz, Aristides I.; Hsu, Raymond Y.
Background: Ankle arthroplasty has emerged as a viable alternative to ankle arthrodesis due in large part to recent advancements in both surgical technique and implant design. This study seeks to document trends of arthroplasty and arthrodesis for ankle osteoarthritis in New York State from 2009-2018 in order to determine if patient demographics play a role in procedure selection and to ascertain the utilization of each procedure and rates of complications. Methods: Patients 40 years and older from 2009-2018 were identified using International Classification of Diseases, Ninth and Tenth Revisions ( ICD-9 and ICD-10 ), Clinical Modification ( CM ) diagnosis and procedure codes for ankle osteoarthritis, ankle arthrodesis, and ankle arthroplasty in the New York statewide planning and research cooperative system database. A trend analysis for both inpatient and outpatient procedures was performed to evaluate the changing trends in utilization of ankle arthrodesis and ankle arthroplasty over time. A multivariable logistic regression was used to assess the odds of receiving ankle arthrodesis relative to ankle arthroplasty. Complications were compared between inpatient ankle arthrodesis and arthroplasty using multivariable Cox proportional hazards regression. Results: A total of 3735 cases were included. Ankle arthrodesis increased by 25%, whereas arthroplasty increased by 757%. African American race, federal insurance, workers compensation, presence of comorbidities, and higher social deprivation were associated with increased odds of having an ankle arthrodesis vs an ankle arthroplasty. Compared with ankle arthroplasty, ankle arthrodesis was associated with increased rates of readmission, surgical site infection, acute renal failure, cellulitis, urinary tract infection, and deep vein thrombosis. Conclusion: Ankle arthroplasty volume has grown substantially without a decrease in ankle arthrodesis volume, suggesting that ankle arthroplasty may be selectively used for a different population of patients than ankle arthrodesis patients. Despite the increased growth of ankle arthroplasty, certain patient demographics including patients from minority populations, federal insurance, and from areas of high social deprivation have higher odds of receiving arthrodesis. Level of Evidence: Level III, retrospective cohort.